Medico-Social Approach to the Development of a Methodology for Assessing the “Quality of Life” after Cataract Phacoemulsification. Part 1 - I. G. Ovechkin; N. I. Ovechkin; A. V. Shakula; A. I. Pavlov; D. F. Pokrovsky (Oftalʹmologiâ, 2022)
Purpose. Scientific substantiation of methodological approaches to the development of a “quality of life” (QoL) questionnaire after cataract phacoemulsification (PEC) in patients with visually stressful work (VLT), based on a “medico-social” health model.Methods. The study was carried out on the basis of methodological standards for the development of new tools for assessing symptoms in clinical medicine developed by specialists from the International Center for the Study of Quality of Life (St. Petersburg). This article presents the first stage of development aimed at the formation of a preliminary version of the questionnaire. The initial volume of questions (complaints) of the patient was carried out in the following areas: individual interviews (according to the standard developed methodology) with 50 patients with ZNT; analysis of proven methods for studying QOL in cataracts (“NEI-VFQ”, “Cataract Symptom Scale”, “Catquest-9SF”, etc.); analysis of proven methods for studying QoL in keratorefractive surgery and asthenopic conditions in patients with RNT; analysis of the classification structure of the International Classification of Functioning (ICF) from the standpoint of the development of characteristic “domains”.Results. The data obtained indicate that a total of 35 patient complaints were identified (7 — “visual”; 6 — “professional”; 16 — “functional”; 4 — “household”; 4 — “medical and psychological”). The fundamental difference between the development of the methodology for assessing the patient’s QoL after performing PE is the use of a “social model” of health, which confirms the leading (46 % of all complaints) place for “functional” manifestations of the patient’s subjective status, based on specific “domains” of the ICF. Along with this, the practical application of the basic provisions of the ICF involves scaling the severity of the patient’s complaints in the context of the ratio of the duration of the complaint to the total active time of the patient with a gradation: “Mild problems” (5–24 %); “Moderate problems” (25–49 %); “Severe problems” (50–95 %); “Absolute problems” (96–100 %).Conclusion. The results of the first stage of the development of the patient’s QoL questionnaire after the FEC testify to the compliance with clinical standards in terms of content validity, since the questions, scales and general content reflect the significance for the patient and important parameters from a clinical and functional point of view. A distinctive feature and scientific novelty of the questionnaire is the use of a “social model” of health based on the development of “domains” of the international classification of functioning, as well as optimization of the procedure for scaling patient responses.